Distinguishing Screening from Diagnostic Mammograms using Medicare Claims Data - Fenton, Joshua J. (2014)
BACKGROUND: Medicare claims data may be a fruitful data source for research or quality measurement in mammography. However, it is uncertain whether claims data can accurately distinguish screening from diagnostic mammograms, particularly when claims are not linked with cancer registry data. OBJECTIVES: To validate claims-based algorithms that can identify screening mammograms with high positive predictive value (PPV) in claims data with and without cancer registry linkage. RESEARCH DESIGN: Development of claims-derived algorithms using classification and regression tree analyses within a random half-sample of bilateral mammogram claims with validation in the remaining half-sample. SUBJECTS: Female fee-for-service Medicare enrollees age 66 years and older who underwent bilateral mammography from 1999 to 2005 within Breast Cancer Surveillance Consortium (BCSC) registries in four states (CA, NC, NH, and VT), enabling linkage of claims and BCSC mammography data (N=383,730 mammograms obtained by 146,346 women). MEASURES: Sensitivity, specificity, and PPV of algorithmic designation of a “screening” purpose of the mammogram using a BCSC-derived reference standard. RESULTS: In claims data without cancer registry linkage, a three-step claims derived algorithm identified screening mammograms with 97.1% sensitivity, 69.4% specificity, and a PPV of 94.9%. In claims that are linked to cancer registry data, a similar three-step algorithm had higher sensitivity (99.7%), similar specificity (62.7%), and higher PPV (97.4%). CONCLUSIONS: Simple algorithms can identify Medicare claims for screening mammography with high predictive values in Medicare claims alone and in claims linked with cancer registry data.